Circulating markers of microbial translocation and host response to bacteria with risk of colorectal cancer: a prospective, nested case-control study in menResearch in context - Mengyao Shi; Xiaoyu Zong; Jinhee Hur; Brenda M. Birmann; Otoniel Martinez-Maza; Marta Epeldegui; Andrew T. Chan; Edward L. Giovannucci; Yin Cao (EBioMedicine, 2023)
Summary: Background: Gut microbial dysbiosis contributes to colorectal cancer (CRC) pathogenesis, possibly mediated in part by increased intestinal permeability to endotoxin lipopolysaccharide (LPS), microbial translocation, and subsequent endotoxemia and inflammation. However, epidemiologic evidence linking circulating markers of microbial translocation with CRC risk is limited. Methods: We conducted a prospective, nested case–control study of 261 incident CRC cases and 261 controls (matched on age and time of blood draw) among 18,159 men with pre-diagnostic blood specimens in the Health Professionals Follow-Up Study (1993–2009). We examined three complementary markers of microbial translocation and host response to bacteria, including LPS-binding protein (LBP), soluble CD14 (sCD14), and endotoxincore antibody (EndoCAb) immunoglobulin M (IgM), with subsequent risk of CRC. Unconditional logistic regressions were used to estimate odds ratios (ORs) and 95% confidence intervals (CIs). Findings: Pre-diagnostic circulating levels of sCD14 were associated with a higher risk of incident CRC. Compared to men in the lowest quartile, the multivariable OR was 1.90 (95% CI, 1.13–3.22) for men in the highest quartile (OR per standard deviation [SD] increase, 1.28; 95%CI 1.06–1.53; Ptrend = 0.01). This positive association remained similar after adjusting for C-reactive protein, interleukin-6, and soluble tumor necrosis factor receptor-2, and within strata of putative CRC risk factors. We also observed a suggestive inverse association between EndoCAb IgM and risk of CRC (OR per SD increase, 0.84; 95%CI 0.69–1.02; Ptrend = 0.09). Interpretation: Microbial translocation and host response to bacteria, as reflected by sCD14, is associated with risk of incident CRC in men. Funding: US National Institutes of Health.